Art. 10c tarczy antykryzysowej – czy to przepis na bezkarność władzy? - Antolak, Wiktor (Czasopismo Prawa Karnego i Nauk Penalnych, 2021)
The study concerns the provision of Article 10c of the so-called anti-crisis shield which excludes criminal liability for behavior related to combating the coronavirus SARS-CoV-2 pandemic. Although this provision has lost its binding force, its temporal scope covers numerous socially significant behaviors the criminal evaluation of which does not seem to be unreasonable. The discussion of this imprecise provision aims to formulate a catalog of premises for the application of this institution which can be useful when circumstances arise that allow authorities for the prosecution of the above-mentioned behaviors. The method of pro-constitutional interpretation turns out to be very important in the context of decoding the normative content of the provision because a literal reading could lead to completely unacceptable effects in a democratic state ruled by law and based on the principle of legalism.